An inquiry into the nature and causes of Climate Wealth of Nations: What temperature finance gravitates towards? Sketching a climate-finance nexus and outlook on climate change-induced finance prospects - Puaschunder, Julia (Archives of Business Research, 2019)
What is the optimal temperature finance gravitates towards? While we have empirical evidence for the optimal cardinal temperature for GDP production and international development links external climate conditions to levels of societal development, no literature exists on climate-induced-finance flows. Research on temperature-dependent financial flows holds invaluable insights in light of climate change. The connection between climate change and finance will be drawn via price mechanisms. Given the extinction potential of crops, industry and service production, price mechanism will be prospected with a hyperbolic tilt towards the end of durability and the closeness to extinction. In contrast to classical and standard approaches in economics to determine prices, the following research thereby takes into account that agents in their behavior can be constrained by shrinking timeframes for production in light of global warming. The contemporary attention to global warming and climate shocks is thereby assumed to affect the price expectations and hence actual market prices of commodities. Paying attention to supply and demand side perspectives, inflated prices surrounding scarcity will be first modelled and then back-tested on data about prices in commodities of food and beverages. Future wealth of nations will be introduced by the concept of climate flexibility defined as the range of temperature variation of a country. So far, a broad spectrum of climate zones has not been defined as asset but climate change will require territories being more flexible in terms of changing economic production. The more climate variation a nation state possesses, this paper argues, the more degrees of freedom a country has in terms of GDP production capabilities in a differing climate. These preliminary insights aid in answering what financial patterns can we expect given predictions the earth will become hotter. Already now this paper presents human capital flows and financial market inflows into areas that are winning economically from a warming globe. The degree of climate flexibility is found to be related to human migration inflow.